Multi-touch Interactions in Finance - Emerson, Christopher James Lawrence (2008)
The aim of this research is to examine the potential use of multi-touch display technology in order to support the analysis of financial time series data. To fully investigate the advantages and disadvantages of the multi-touch technology in a financial charting context, a multi-touch display was constructed along with a comprehensive software package for performing multi-touch interactive chart analysis and annotation. The multi-touch enabled prototype was then directly compared to a traditional mouse-driven user interface and compared on a like for like basis using GOMS analysis techniques. The results of this research show that multi-touch technology can be successfully applied in this domain, and that multi-touch user interfaces might also be beneficial to users.